2013
DOI: 10.1371/journal.pone.0070531
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution Transcriptomic Analyses of Sinorhizobium sp. NGR234 Bacteroids in Determinate Nodules of Vigna unguiculata and Indeterminate Nodules of Leucaena leucocephala

Abstract: The rhizobium-legume symbiosis is a model system for studying mutualistic interactions between bacteria and eukaryotes. Sinorhizobium sp. NGR234 is distinguished by its ability to form either indeterminate nodules or determinate nodules with diverse legumes. Here, we presented a high-resolution RNA-seq transcriptomic analysis of NGR234 bacteroids in indeterminate nodules of Leucaena leucocephala and determinate nodules of Vigna unguiculata. In contrast to exponentially growing free-living bacteria, non-growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
63
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 91 publications
6
63
0
1
Order By: Relevance
“…Our data are in agreement with earlier findings reported for planktonic Bradyrhizobium japonicum cells and for S. meliloti suggesting that flagella play a pivotal role during root colonization but that they are most likely not essential during the infection process (56)(57)(58)(59). This hypothesis fits well with the recent observation that flagellar genes are downregulated in bacteroids in NGR234 (29) and with the observation that flagellar genes are subject to QS-mediated regulation in S. meliloti (60,61).…”
Section: Fig 2 Venn Diagram Showing the Overlap Of Differentially Expsupporting
confidence: 91%
See 3 more Smart Citations
“…Our data are in agreement with earlier findings reported for planktonic Bradyrhizobium japonicum cells and for S. meliloti suggesting that flagella play a pivotal role during root colonization but that they are most likely not essential during the infection process (56)(57)(58)(59). This hypothesis fits well with the recent observation that flagellar genes are downregulated in bacteroids in NGR234 (29) and with the observation that flagellar genes are subject to QS-mediated regulation in S. meliloti (60,61).…”
Section: Fig 2 Venn Diagram Showing the Overlap Of Differentially Expsupporting
confidence: 91%
“…Recently, it was also shown that the T3SS-I locus was upregulated in the Leucaena leucocephala and V. unguiculata bacteroids. Transcription was, however, highest in the L. leucocephala nodules in comparison to the V. unguiculata nodules (29). Within this framework, our transcriptome study suggests that the T3SS-I is subject to a QS-independent regulation.…”
Section: Fig 2 Venn Diagram Showing the Overlap Of Differentially Expmentioning
confidence: 56%
See 2 more Smart Citations
“…Plant shoots were dried at 65°C for 5 days and then used for determining shoot dry weight per plant. For electron microscopy, ultrathin sections of 1-month nodules from soybeans were prepared and observed in a JEM-1230 transmission electron microscope as described earlier (31). To check nodule occupation, S. fredii mutants were individually mixed with the wild-type strain (or the mutant indicated) in an equal quantity (OD 600 , 0.2; 1-ml volume) and inoculated on soybeans.…”
Section: Methodsmentioning
confidence: 99%